Tumor vascular changes mediated by inhibition of oncogenic signaling. - Qayum, N; Muschel, R; Im, J; Balathasan, L; Koch, C; Patel, S; Mckenna, W; Bernhard, E (2009)
Many inhibitors of the epidermal growth factor receptor (EGFR)-RAS-phosphatidylinositol 3-kinase (PI3K)-AKT signaling pathway are in clinical use or under development for cancer therapy. Here, we show that treatment of mice bearing human tumor xenografts with inhibitors that block EGFR, RAS, PI3K, or AKT resulted in prolonged and durable enhancement of tumor vascular flow, perfusion, and decreased tumor hypoxia. The vessels in the treated tumors had decreased tortuosity and increased internodal length accounting for the functional alterations. Inhibition of tumor growth cannot account for these results, as the drugs were given at doses that did not alter tumor growth. The tumor cell itself was an essential target, as HT1080 tumors that lack EGFR did not respond to an EGFR inhibitor but did respond with vascular alterations to RAS or PI3K inhibition. We extended these observations to spontaneously arising tumors in MMTV-neu mice. These tumors also responded to PI3K inhibition with decreased tumor hypoxia, increased vascular flow, and morphologic alterations of their vessels, including increased vascular maturity and acquisition of pericyte markers. These changes are similar to the vascular normalization that has been described after the antiangiogenic treatment of xenografts. One difficulty in the use of vascular normalization as a therapeutic strategy has been its limited duration. In contrast, blocking tumor cell RAS-PI3K-AKT signaling led to persistent vascular changes that might be incorporated into clinical strategies based on improvement of vascular flow or decreased hypoxia. These results indicate that vascular alterations must be considered as a consequence of signaling inhibition in cancer therapy.